Esophageal Endoscopic Submucosal Dissection Assisted by an Overtube with a Traction Forceps: An Animal Study. (27th July 2016) - Ohata, Ken; Fu, Kuangi; Sakai, Eiji; Nonaka, Kouichi; Tashima, Tomoaki; Minato, Yohei; Ohno, Akiko; Ito, Takafumi; Tsuji, Yosuke; Chiba, Hideyuki; Yamawaki, Makoto; Hemmi, Hideyuki; et al.
Abstract : Esophageal endoscopic submucosal dissection (ESD) is technically difficult. To make it safer, we developed a novel method using overtube with a traction forceps (OTF) for countertraction during submucosal dissection. We conducted an ex vivo animal study and compared the clinical outcomes between OTF-ESD and conventional method (C-ESD). A total of 32 esophageal ESD procedures were performed by four beginner and expert endoscopists. After circumferential mucosal incision for the target lesion, structured as the isolated pig esophagus 3 cm long, either C-ESD or OTF-ESD was randomly selected for submucosal dissection. All the ESD procedures were completed as en bloc resections, while perforation only occurred in a beginner's C-ESD procedure. The dissection time for OTF-ESD was significantly shorter than that for C-ESD for both the beginner and expert endoscopists (22.8 ± 8.3  min versus7.8 ± 4.5  min, P < 0.001, and11.3 ± 4.4  min versus5.9 ± 2.5  min, P = 0.01, resp.). The frequency and volume of the submucosal injections were significantly smaller for OTF-ESD than for C-ESD (1.3 ± 0.6 times versus2.9 ± 1.5 times, P < 0.001, and5.3 ± 2.8  mL versus15.6 ± 7.3  mL, P < 0.001, resp.). Histologically, muscular injury was more common among the C-ESD procedures (80% versus 13%, P = 0.009 ). Our results indicated that the OTF-ESD technique is useful for the safe and easy completion of esophageal ESD.